Evaluation of the Knowledge, Attitude, and Practice of Pregnant Women in the COVID-19 Outbreak in Mahdiyeh Hospital - Naeiji, Zahra; Moridi, Atefeh; Meshkat, Maryam; Rahmati, Nayereh; Ashrafivand, Sepideh (Novelty in Biomedicine, 2023)
Background: As observed in severe acute respiratory syndrome (SARS) and Meddle-East respiratory syndrome (MERS) epidemics, pregnant women are more prone to complications and adverse outcomes of coronavirus infection. Coronavirus disease 2019 (COVID-19) is thought to significantly increase the risks to maternal and fetal health, while others believe that pregnant women have similar morbidity and mortality compared to the general population. Due to the severe prognosis of pregnant women with SARS-Coronavirus (CoV) or MERS-CoV, many concerns have been raised about the effects of SARS-CoV-2 on this sensitive group of patients. Materials and Methods: The present study was a cross-sectional descriptive study that was performed on all pregnant women referred to Mahdieh Hospital in Tehran, Iran, whose gestation period was during the coronavirus epidemic, by the available sampling method. Pregnant women answered the questions asked by the researcher and the answers were recorded in a pre-prepared structured standard questionnaire. Questionnaire questions included basic information, knowledge, attitude, practice, and obstacles. Results: A total of 284 people participated in this study with a mean age of 29.6 ± 12.2 years. The mean gestational age among the participants in this study was 28.5 ± 9.7 weeks. The knowledge, attitude, and practice of pregnant women referred to Mahdieh Hospital in Tehran were 74.05, 61.13, and 60.06, respectively. In terms of attitude, improving one’s attitude towards herself will have the greatest effect on improving one’s attitude. According to this finding, the attitude of individuals increases the level of knowledge about COVID-19. The amount of knowledge has a direct positive and significant effect on practice. Also, the attitude has a direct positive and significant effect on the practice. Conclusion: Given that the source of information for most of the participants in this study about COVID-19 was the media. Transmission of correct health information about the relationship between pregnancy and COVID-19, to this sensitive group, through the media could be appropriate. This is important because most participants feel they are at higher risk of developing the disease than non-pregnant people due to their pregnancy status.